Exon 46-48 Deletion of DMD Gene - A Boon in Beckers Muscular Dystrophy - Kulkarni, Trimal; Charki , Siddu; Kalyanshettar, Siddarameshwar S; Patil, Shankargouda V; Patil, Mallangouda M (Journal of Nepal Paediatric Society, 2021)
Becker's muscular dystrophy (BMD) has wide spectrum of presentation from asymptomatic to severe progressive muscular weakness. Subtle weakness can be missed in busy outpatient units. Traditionally muscle biopsy is used for definitive diagnosis. But it is invasive and less helpful in genetic counseling of inherited dystrophinopathies compared to genetic studies. Newer techniques like next generation sequencing (NGS) also help in understanding many phenotype-genotype co-relations. We describe here a seven year boy who presented with mild weakness, without any evidence of cardiomyopathy and had exon 46 - 48 deletion on NGS.